HPV11E6/E7 induces nasal epithelial hyperplasia through JAK2/STAT3 signaling pathway - Yi Zhang; Kaisai Tian; Liying Zheng; Gaohan Zhu; Runyu Zhao; Enhui Zhou; Xiaocheng Xue; Shuixian Huang; Xiaoping Chen; Baoji Hu; Wenhao Yao (European Journal of Medical Research)
Abstract Objectives Nasal mucosal epithelial hyperplasia can cause nasal hyperplastic diseases, more studies have confirmed that different subtypes of HPV infection play a significant role in nasal proliferative diseases, especially nasal inverted papilloma (NIP). This study aims to elucidate the role and mechanism of the HPV11 subtype in regulating nasal epithelial hyperplasia. Methods In our previous study, the expression of HPV infection in NIP was analyzed by Flow-through hybridization and gene chip (HybridMax), with the highest expression rate observed for the HPV11 subtype. Therefore, we aimed to overexpress HPV11E6/E7 in nasal mucosal epithelial cells (HNEpC) to verify the regulatory role and mechanism of HPV11 in nasal epithelial hyperplasia at the cellular level. In this manuscript, we constructed a lentiviral vector overexpressing HPV11E6/E7 and transfected it into HNEpC. We used HNEpC as the control group and HPV11E6/E7-overexpressing cells as the experimental group. Cell proliferation was assessed using CCK-8, EdU, and colony formation assays. Cell migration ability was evaluated by wound healing and Transwell assays. Protein expression levels related to apoptosis, epithelial–mesenchymal transition (EMT), and the JAK2/STAT3 pathway were analyzed by western blot. Results The results showed that overexpression of HPV11E6/E7 significantly increased the proliferation and migration of nasal epithelial cells, promoted the progression of EMT, and inhibited cell apoptosis. Further verification showed that the overexpression of HPV11E6/E7 significantly promoted the activation of the JAK2/STAT3 signaling pathway. Conclusions In summary, we found that low-risk subtype HPV11 promotes nasal mucosal epithelial hyperplasia and malignant progression by increasing activation of the JAK2/STAT3 pathway. The JAK2/STAT3 pathway has been prioritized due to its established role in promoting cell proliferation and EMT in HPV-related diseases.